Ovarian Endometrioma Negatively Impacts Oocyte Quality and Quantity But Not Pregnancy Outcomes in Women Undergoing IVF/ICSI Treatment: A Retrospective Cohort Study - Wu, Yaoqiu; Yang, Rong; Lan, Jie; Lin, Haiyan; Jiao, Xuedan; Zhang, Qingxue (Frontiers in Endocrinology, 2021)
Purposes: To determine the impact of ovarian endometrioma per se on in vitro fertilization/ intracytoplasmic sperm injection (IVF/ICSI) outcomes. Methods: This retrospective study was conducted on 862 infertile women who had ovarian endometriomas and underwent their first ovarian stimulation for IVF/ICSI treatment between January 2011 to December 2019 at a public university hospital. A non-endometrioma comparison group, comprising 862 women with other infertility factors, was matched according to age, body mass index (BMI) and infertility duration. Ovarian reserve and response and pregnancy outcomes between the two groups were analyzed. Multivariate logistic regression (MLR) analysis was conducted on the basis of clinical covariates assessed for their association with live birth. Results: The results showed that significantly lower antral follicle count (AFC), anti-Müllerian hormone (AMH), ovarian sensitivity index (OSI), oocytes maturation and fertilization rates, blastocyst rate, number of oocytes retrieved, and available embryos were found in women with endometrioma compared with the control, respectively (P < 0.05). The cumulative live birth rate per patient in women with endometrioma was lower than that of women without endometrioma (39.32% vs 46.87%, P = 0.002). In women with endometrioma, those who underwent surgical intervention prior to IVF/ICSI treatment had higher maturation (86.03% vs 83.42%, P = 0.003), fertilization (78.16% vs 74.93%, P = 0.004), and top-quality embryo rates (42.94% vs 39.93%, P = 0.097), but had fewer oocytes retrieved (8.01± 5.70 vs 9.12 ± 6.69, P = 0.013), than women without surgery. However, live birth rates were comparable between women with endometrioma and women in the control group, regardless of whether they had a prior history of ovarian surgery. MLR analysis showed no correlation between endometrioma per se and live birth after being adjusted for number of top-quality embryos transferred and stage of embryo transfer. Conclusions: The study supported the conclusion that ovarian endometrioma negatively impacts oocyte quality and quantity, but not overall pregnancy outcomes, in women undergoing IVF/ICSI treatment. Endometrioma lowers the cumulative live birth rate by decreasing the number of embryos. Surgical excision of endometrioma prior to IVF/ICSI can partly improve oocyte maturation and fertilization rates, but not pregnancy outcomes.